2015
DOI: 10.1111/jonm.12312
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement in nursing: an integrative review of the literature

Abstract: Nursing managers and leaders may promote improvements in leadership behaviours and a context of optimism and self-efficacy as a way of increasing work engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
183
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(216 citation statements)
references
References 54 publications
16
183
0
17
Order By: Relevance
“…[10] In this context, Chaudhary et al, (2011) underlined, employee engagement has developed as one path for organizations to gauge their interest in human capital. [26] Besides, Sierra et al (2015) proposed that positive work atmosphere, supportive organization and leadership styles are factors that encouraging work engagement. [27] As regarding job insecurity, the result of this study revealed that nurses perceive a lower level of job insecurity, however, affective job insecurity had slightly a higher mean than cognitive job insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In this context, Chaudhary et al, (2011) underlined, employee engagement has developed as one path for organizations to gauge their interest in human capital. [26] Besides, Sierra et al (2015) proposed that positive work atmosphere, supportive organization and leadership styles are factors that encouraging work engagement. [27] As regarding job insecurity, the result of this study revealed that nurses perceive a lower level of job insecurity, however, affective job insecurity had slightly a higher mean than cognitive job insecurity.…”
Section: Discussionmentioning
confidence: 99%
“…Such a low level of work engagement might be problematic for management of staff midwives working on maternity and labor wards. García-Sierra et al [21] highlighted the importance of managers' leadership at the ward level for promoting staff midwives' work engagement. In general, work engagement and burnout were reported to have a crossover effect.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of professional efficacy refers to a tendency to negatively evaluate one's work with recipients such as students, pupils, clients, patients, consumers or delinquents, and is accompanied by feelings of inadequacy toward one's work [32]. Work engagement of staff nurses was reported to comprise four influencing factors (impact of nurse managers, organizational antecedents, individual antecedents, and outcomes of engagement), among which individual antecedents included personal traits and family issues other than professional characteristics [21]. Although work engagement and professional efficacy express a positive attitude toward working, there was some difference in their significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement has been empirically shown to influence nursing performance, with the consequent impact on health care results [5]. From a psychological point of view, engagement leads to subjective wellbeing [6], as it allows an individual to enter a flow state [7] and satisfy basic psychological needs of autonomy and competence [8,9].…”
Section: Introductionmentioning
confidence: 99%